2012
DOI: 10.1007/s10534-012-9533-y
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum ammonium sulfate dodecahydrate purified from traditional Chinese medicinal herb Korean monkshood root is a potent matrix metalloproteinase inhibitor

Abstract: Matrix metalloproteinases (MMPs) are zinc-dependent endopeptidases and key regulators for many physiological and pathological functions. The MMP inhibitors have been shown to modulate diseases such as cancer, inflammation, and cardiovascular diseases. In this paper we tracked the MMP inhibitory activities of the traditional Chinese medicinal herb Korean Monkshood Root. The purified active ingredient was identified by the elemental analysis, infrared spectrum (IR) and X-ray diffraction as aluminum ammonium sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Given their antibacterial, antiviral, and antitumor activities, the 3-valent lanthanide compounds play an important role in disease-associated biological processes. [23][24][25][26][27] The interaction of the europium ion (Eu 3+ ) with the protein a-amylase, an important digestive enzyme in saliva and pancreatic juice, has been studied over wide ranges of pH and concentration. The protein provides three independent, noncooperative binding sites for Eu 3+ .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given their antibacterial, antiviral, and antitumor activities, the 3-valent lanthanide compounds play an important role in disease-associated biological processes. [23][24][25][26][27] The interaction of the europium ion (Eu 3+ ) with the protein a-amylase, an important digestive enzyme in saliva and pancreatic juice, has been studied over wide ranges of pH and concentration. The protein provides three independent, noncooperative binding sites for Eu 3+ .…”
Section: Introductionmentioning
confidence: 99%
“…22 The antibacterial and antiviral activities of lanthanide element organic coordination compounds have also been investigated. 25 We previously showed that trivalent aluminum salts and iron salts exert inhibitory effects on MMPs and hinder the tumor migration and metastasis without affecting cell viability 26,27 . However, the inhibitory effects of the 3-valent lanthanide compounds on MT1-MMP and the protein's related diseases have been rarely explored.…”
Section: Introductionmentioning
confidence: 99%
“…This was the first time that an inorganic substrate, i.e. aluminum ammonium sulfate, has been demonstrated to exhibit MMP inhibitory activity, potent enough to interfere with MMP related cellular processes [31].Human matrix metallopeptidase 13 (MMP-13), also known as collagenase-3, represents a key member of the MMP family and has been identified as an important target for the treatment of osteoarthritis (OA) [32][33][34][35]. Until now, MMP-13 inhibitors have been identified mainly viahigh-throughput screening (HTS) in the synthetic compound library.…”
mentioning
confidence: 98%
“…This was the first time that an inorganic substrate, i.e. aluminum ammonium sulfate, has been demonstrated to exhibit MMP inhibitory activity, potent enough to interfere with MMP related cellular processes [31].…”
mentioning
confidence: 99%
See 1 more Smart Citation